Understanding farmer knowledge and site factors in relation to soil-borne pests and pathogens to support agroecological intensification of smallholder bean production systems - Ngoya, Zuwena J.; Mkindi, Angela G.; Vanek, Steven J.; Ndakidemi, Patrick A.; Stevenson, Philip C.; Belmain, Steven R. (Frontiers in Sustainable Food Systems, 2023)
Introduction Pests and diseases limit common bean (Phaseolus vulgaris) production in intensifying smallholder farming systems of sub-Saharan Africa. Soil-borne pests and diseases (SPD) are particularly challenging for farmers to distinguish and manage in cropping systems that vary in terms of soils, farmer knowledge, and management factors. Few studies have examined soil drivers of SPD in smallholder systems, integrated with farmers' perceptions and management practices. Methods In Kilimanjaro, Tanzania, we assessed farmer knowledge and SPD management for common bean alongside soil type and soil quality. Focus group discussions and field survey findings including farmer observations and soil nutrient balances were integrated with soil analyses of farmers' fields. Multiple correspondence analysis (MCA) and principal component analysis (PCA) assessed relationships among farmer demographics, pests and diseases, soil characteristics, and management practices. Results and discussion Surveys revealed that 100% of farmers knew of the bean foliage beetle (Ootheca bennigseni) but few recognized the soilborne pest Ophiomyia spp. or bean fly despite it being more destructive. About a third of farmers knew of root rot diseases caused by Pythium spp. and Fusarium spp. Synthetic pesticides were used by 72% of farmers to control pests, while about half that (37%) used pesticidal plants, particularly Tephrosia vogelii extracts sprayed on foliage. Regarding SPD, 90% of farmers reported that their management practices were ineffective. Meanwhile, synthetic fertilizers were used by nearly all farmers in beans intercropped with maize (Zea mays), whilst very few farmers used manure or compost. Soil available phosphorus was lowbut showed a balance between inputs and outputs regardless of whether fields were owned. Field nitrogen balances were more negative when fields were owned by farmers. An MCA showed that older farmers employed a greater number of pest control practices. The PCA showed that field variability was dominated by soil organic matter, elevation, and soil pH. Higher organic matter levels were also associated with less stunting and wilting of beans observed by farmers. Our results suggest that research and farmer learning about SPD ecology are key gaps, alongside recycling of organic residues to soils. Cost-effective and sustainable practices to manage bean SPDs for smallholders are also needed.